ANTIBACTERIAL EFFECT OF EUGENIA POLYANTHA WIGHT WITH CORYNEBACTERIUM DIPHTHERIAE NON-TOXIGENIC - Murbarani, Ivita T; Isbandiati, Endang; Puspitasari, Chrisdina (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Corynebacterium diphtheriae is a bacteria that causes diphtheria. In recentyears, the bacterium is resistant to antibiotics. Eugenia polyantha wight might be a suitableantibiotic alternative as it has antibacterial effect against Staphylococcus aureus. The contentof the antibacterial compound in Eugenia polyantha wight at specific concentrations isexpected to be able to kill the Corynebacterium diphtheriae.Purpose: This study aimed to examine the antibacterial effect of Eugenia polyantha wight toCorynebacterium diphtheriae non-toxic.Method: Bay leaf extract (Eugenia polyantha wight) made with maceration method. Thisresearch is an experimental study conducted in vitro using a microdilution test on 96 wellplates then count value with the streaking method to find out MBC.Results: bactericidal power was quite effective at the concentration of 40%, while at the concentrationof 80%-100% has very strong bactericidal power that could destroy the growth of bacteria 99.9%. Thehigher the concentration of bay leaves extract, the higher the bactericidal power of bacteria Conclusion: Eugenia polyantha wight has an antibacterial effect against Corynebacteriumdiphtheriae non-toxic.